Development and evaluation of sub-element testing of SiC/SiC ceramic matrix composites at elevated temperatures. Issue 5 (May 2021) - Gale, L.; Harris, S.; Pattison, S.; Baker, J.; Fowler, J.
Abstract: SiC/SiC ceramic matrix composites (CMCs) are being developed for use in aero-engines to replace nickel superalloy components. Sub-element testing acts as the key stepping stone in bridging understanding derived from basic coupon testing and more complex component testing. This study presents the development of high temperature C-shape sub-element testing with the use of digital image correlation to study damage progression. The specimen is designed with a bias towards a mixed mode-stress state more similar to what a CMC component may see in service. Both monotonic and fatigue tests were completed on C specimens and compared with predicted behaviour from modelling. Test data from both test types suggested that specimens were failing once they reached a critical radial stress level. However evidence from fractography of specimens showed that in both monotonic and fatigue tests radial cracks (driven by hoop stresses) are initiating prior to circumferential cracks.